2021
DOI: 10.1093/pubmed/fdab055
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 community care in Israel—a nationwide cohort study from a large health maintenance organization

Abstract: Background Among the many medical challenges presented by the COVID-19 pandemic, management of the majority of patients in community outpatient settings is crucial. The aim of this study was to describe the characteristics and outcomes among confirmed COVID-19 cases who were managed at three settings: two outpatient settings and one inpatient. Methods A retrospective database cohort study was conducted in a large Israeli Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The criteria for hospital admission of patients with covid-19 in Israel were consistent throughout the study period, in accordance with guidelines set by the Ministry of Health. 37 To distinguish between new outcomes and existing ones, we further excluded patients who had the considered outcome before the PCR test (index date). However, the exclusion criteria were different for different outcome types: for outcomes reflecting a chronic state (for example, asthma, diabetes), we excluded patients with any occurrence of that outcome in the past; for outcomes reflecting a temporary state (for example, cough, weakness) we excluded patients with occurrence of that outcome in the previous year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for hospital admission of patients with covid-19 in Israel were consistent throughout the study period, in accordance with guidelines set by the Ministry of Health. 37 To distinguish between new outcomes and existing ones, we further excluded patients who had the considered outcome before the PCR test (index date). However, the exclusion criteria were different for different outcome types: for outcomes reflecting a chronic state (for example, asthma, diabetes), we excluded patients with any occurrence of that outcome in the past; for outcomes reflecting a temporary state (for example, cough, weakness) we excluded patients with occurrence of that outcome in the previous year.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded from the study all patients who were admitted to hospital with covid-19 during the 30 days after infection, aiming to investigate long covid in patients with mild disease. The criteria for hospital admission of patients with covid-19 in Israel were consistent throughout the study period, in accordance with guidelines set by the Ministry of Health 37. To distinguish between new outcomes and existing ones, we further excluded patients who had the considered outcome before the PCR test (index date).…”
Section: Methodsmentioning
confidence: 99%
“…In Israel, most patients with SARS-CoV-2 infection or symptomatic COVID-19 were treated in the community, either by centralized remote COVID-19 managed care programs (by physicians and nurses) or by the patient's personal primary care physician (PCP) (each physician treating his/her own patients) [2]. The same process happened in primary care throughout nations [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there was no association between several comorbidities and reporting side effects. Considering that older age and certain underlying medical conditions are major risk factors for severe illness from COVID-19 [ 21 , 22 ], it is particularly important in this group of patients to underline that side effects are mild and therefore not an indication to avoid vaccination. Interestingly, we found that the fact of being pregnant at vaccination reduced the reporting ratio of all symptoms when compared with randomly matched controls.…”
Section: Discussionmentioning
confidence: 99%